Filozofia wolna od uprzedzeń. 60 lat czasopisma filozoficznego "Studia Philosophiae Christianae" - Adam Świeżyński (Studia Philosophiae Christianae)
The year 2025 marks the 60th anniversary of the founding of the philosophical journal Studia Philosophiae Christianae (SPCh). It is one of the longest-running philosophical journals in Poland. The journal was established in 1965 on the initiative of the members of the Faculty of Christian Philosophy at the Academy of Catholic Theology in Warsaw. It is currently being edited at the Institute of Philosophy at the Cardinal Stefan Wyszynski University in Warsaw, into which the Academy of Catholic Theology was transformed in 1999. The journal is published biannually, although for a period it was also published quarterly. From the very beginning, it has published texts from all branches of philosophy, and initially also from psychology. During the 1960s and 1970s, a number of texts were published that expressed differing views from the Marxist philosophy that was dominant in Poland at that time. Currently, in SPCh are published articles on philosophy, reviews of philosophical books, and reports on philosophical events. The journal motto is: “Philosophy free from bias.” It reflects commitment to intellectual humility and the open exchange of ideas. In this way, it is emphasized that the journal is open to different schools of thought and argumentation, including those far removed from Christian inspiration. The specificity of the journal is the publication of texts in the field of classical philosophy, in particular its continuity with Christian philosophy broadly understood, falling within the scope of theoretical and practical philosophy. This specificity may be understood through the history of the journal, as well as the worldview of the academic center where it has been published since its beginning. The name of the journal is also inspired by its historical roots, while also aiming to reflect its distinctive character. However, this does not imply that it is exclusive to other philosophical traditions, including those influenced by different worldviews as well as cultural and religious contexts. The article presents the history of the SPCh, its specific character, the topics of the published texts, and their authors.